2017
DOI: 10.1016/j.mce.2017.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR-29b-1/a transcription and identification of target mRNAs in CHO-K1 cells

Abstract: miR-29b and miR-29a transcript levels were reported to increase in exponentially growing CHO-K1 cells. Here, we examine the regulation of miR-29b-1/a in CHO-K1 cells. We observed that 4-hydroxytamoxifen (4-OHT) increased pri-miR-29b-1 and pri-miR-29a transcription in CHO-K1 cells by activating endogenous estrogen receptor α (ERα). DICER, an established, bona fide target of miR-29b-1/a, was shown to be regulated by 4-OHT in CHO-K1 cells. We showed that miR-29b-1 and miR-29a serve a repressive role in cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In our study, immunofluorescence analysis and transfection experiments using miRNA analogues suggested that these miRNAs might not only regulate genes that modulate the composition of ECM such as MMPs and TIMPs, but might also play a role in the alteration of hormonal activities via modifying the gene expression of estrogen and progesterone receptors. Consistent with our results, a few previous reports suggested that these miRNAs affect the receptivity of estrogen and progesterone receptors [ 43 , 44 , 45 , 46 , 47 ]. Our results suggest that miRNAs might play a role in the development of ULs via the regulation of the hormonal micro-environment and composition of ECM.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, immunofluorescence analysis and transfection experiments using miRNA analogues suggested that these miRNAs might not only regulate genes that modulate the composition of ECM such as MMPs and TIMPs, but might also play a role in the alteration of hormonal activities via modifying the gene expression of estrogen and progesterone receptors. Consistent with our results, a few previous reports suggested that these miRNAs affect the receptivity of estrogen and progesterone receptors [ 43 , 44 , 45 , 46 , 47 ]. Our results suggest that miRNAs might play a role in the development of ULs via the regulation of the hormonal micro-environment and composition of ECM.…”
Section: Discussionsupporting
confidence: 93%
“…miR-29a is described in literature as upregulated in CHO cells during exponential growth phase (Klanert et al 2016 ), which is what we also observe as an enriched presence in the respective exosome samples. However, others also claim a growth-inhibitory effect of this miRNA for CHO cells (Bort et al 2012 ; Muluhngwi et al 2017 ). Similar applies to miR-378, which we found to be enriched in CHO exosomes and that is presumably growth-inhibitory species, since its depletion can increase growth and cell density of CHO cells (Coleman et al 2018 ; Costello et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…aberrant expression of miR-29b-1 and miR-29a reduced CHO-K1 cell proliferation, colony formation, and cell invasion. In addition, increased miR-29b-1/a expression reduced mRNA and protein levels in Disher ( Muluhngwi et al, 2017 ).…”
Section: Mechanism Of Mirna Affecting the Expression Of Recombinant P...mentioning
confidence: 99%